2008
DOI: 10.1002/cbdv.200890195
|View full text |Cite
|
Sign up to set email alerts
|

KP1019, A New Redox‐Active Anticancer Agent – Preclinical Development and Results of a Clinical Phase I Study in Tumor Patients

Abstract: The promising drug candidate indazolium trans-[tetrachlorobis(1H-indazole)ruthenate(III)] (KP1019) is the second Ru-based anticancer agent to enter clinical trials. In this review, which is an update of a paper from 2006 (Hartinger et al., J. Inorg. Biochem. 2006, 100, 891-904), the experimental evidence for the proposed mode of action of this coordination compound is discussed, including transport into the cell via the transferrin cycle and activation by reduction. The results of the early clinical developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
598
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 785 publications
(614 citation statements)
references
References 75 publications
10
598
1
5
Order By: Relevance
“…indazole)ruthenate(III)] (KP1019) [5] and its sodium salt (NKP1339/IT-139) [6] are under clinical evaluations with promising results. It has been recently reported that the catalytic activity of the [Ru(II)( 6 -p-cymene)] complexes of sulfonamido ethyleneamine ligands can be transferred in cancer cells, which has influence on the extent of intracellular conversion of NAD + to NADH.…”
Section: Compounds Namely Imidazolium Trans-[tetrachlorido(dmso)(imimentioning
confidence: 99%
“…indazole)ruthenate(III)] (KP1019) [5] and its sodium salt (NKP1339/IT-139) [6] are under clinical evaluations with promising results. It has been recently reported that the catalytic activity of the [Ru(II)( 6 -p-cymene)] complexes of sulfonamido ethyleneamine ligands can be transferred in cancer cells, which has influence on the extent of intracellular conversion of NAD + to NADH.…”
Section: Compounds Namely Imidazolium Trans-[tetrachlorido(dmso)(imimentioning
confidence: 99%
“…In spite of the clinical success of cisplatin, cis-diamminedichloridoplatinum(II), and its derivatives there is an on-going demand for the development of novel types of antitumor agents due to the two main disadvantages of these Pt-containing drugs; namely the low efficacy against widespread tumors, intrinsic and acquired resistance of neoplams and severe side effects accompanying tumors [1][2][3] [5] and its sodium analogue KP1339 [6], which are active against a variety of solid tumors. These Ru compounds exhibit low general toxicity, which contrasts to the pharmacological properties of Pt drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Ruthenium compounds are currently considered the most likely candidates for the next generation of metal-based anticancer drugs [2,3]. Two representatives of this class of compounds have entered clinical trials so far: imidazolium trans-[tetrachlorido(dimethylsulfoxide)(1H-imidazole)ruthenate(III)] (NAMI-A) [4,5] and indazolium trans-[tetrachloridobis(1H-indazole)ruthenate(III)] (KP1019) [6][7][8] (see Chart 1 for structures). Only very moderate toxicities were observed in the case of KP1019 [6,7,9] whereas NAMI-A treatment was accompanied by painful blister formation at higher dosage, however that is actually higher than the advised dosage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Chart 1 KP1019 shows remarkable antineoplastic activity against a wide number of preclinical tumor models, including cisplatin resistant colorectal tumors and some primary explanted human tumors [2,6,11,12]. Although the pharmacological target for antitumor ruthenium compounds has not been unequivocally identified, it is unlikely that their modes of action are similar to that of cisplatin [7].…”
Section: Introductionmentioning
confidence: 99%